Numerical simulation of an oscillating water column wave energy converter with and without damping - Didier, E. (2011)
This paper presents numerical simulations that predict the action of a regular incident wave on a simplified Oscillating Water Column Ocean Wave Energy Converter (OWC-OWEC) model. This model is a vertical tube of small circular cross-section placed in the longitudinal symmetry plane of the flume. The paper presents a comparison of numerical results, obtained by a Reynolds-Average-Navier-Stokes (RANS) solver, with experimental data obtained in a wave flume. The numerical code uses a finite-volume method to solve the RANS equations and the Volume of Fluid (VOF) approach to capture the water free surface. The OWC power output is estimated by the pressure drop across the dissipative device (turbine) times the volume flow rate. In the physical model, the turbine’s damping effect was simulated by a piece of porous membrane (textile) placed at the top of the vertical tube. To simulate this dissipative effect in the numerical simulations, a pressure drop at the top boundary of the vertical cylinder was imposed. The water free-surface elevation time-series, inside and outside of the cylinder, and the resulting amplification factor obtained by the numerical code are compared with the experimental data for a regular incident wave with 0.015m height and frequency between 0.55 and 1.6Hz. Good concordance is obtained between numerical and experimental results, as it was also found in previous studies for the same configuration without damping.